Mixed infection of peste-des-petits ruminants and Capripox in goats in south Kivu, Democratic Republic of Congo - Birindwa, B.A.; Gitao, C.G.; Bisimwa, P.N.; Okafor, C.; Bebora, C.L. (ScopeMed, 2017)
Objective: We aimed at determining the prevalence and characterizing the CaPV, determining the CaPV-PPRV coinfection prevalence and providing data about phylogenetic relationship between the fusion protein of PPRV and P32 gene of CaPV. Materials and methods: A total of 150 samples including animals swabs, tissues and blood were collected from unvaccinated goats in a PPR and/or Capripox outbreaks in South Kivu, Eastern of Democratic Republic of the Congo. Conventional PCR and reverse transcriptase (RT-PCR) were used respectively to amplify P32, RPO30, GPCR genes of Capripox virus and Fusion (F) protein of PPRV. Positive samples were sequenced for phylogenetic analysis. Results: Out of 150 tested animals, 64.7% (n=97/150) were PPRV positive, 52.7% (n=79/150) were Capripox positive and 38.7% (n=58/150) were positive for both PPRV and CaPV. The pairwise comparison of P32gene of CaPV and F gene of PPRV showed 99.75% of identity percentage among goatpox virus sequences, 96.95% among PPRV sequences and 47.91% between CaPV and PPRV sequences. Conclusion: The study has demonstrated high prevalence of CaP V-PPRV mixed infection in South Kivu. Lumpy skinvirus disease (LSVD) is a lineage circulating which has a genetic relationship between its P32gene and the Fgene of PPRV giving the challenge to differentiate the two diseases at the clinical farm level.